Digital Lipoma: Retrospective Evaluation of Cases in a Reference Center - Beşir Öner, Mehmet; Yalçın, Can Ege; Çelik, Uğur; Çınar, Fatih; Çomunoğlu, Nil; Çetinkale, Oğuz (Cerrahpaşa Medical Journal, 2024)
Objective: Although lipomas are the most common benign soft tissue tumors, they are rarely found in the hand and are exceptionally rare on the fingers. Therefore, the purpose of this study was to investigate lipomas in atypical locations to aid in the differential diagnosis of finger tumors. Methods: We retrospectively examined a cohort of 20 patients who were diagnosed with lipomas on the fingers. The diagnosis was made through clinical and imaging examinations. Surgical intervention was based on symptoms such as pain, paresthesias, functional impairment, or aesthetic concerns. Results: Lipomas were more likely to be located on the third finger of the right hand, and most common pathological subtype was fibrolipoma. One giant lipoma was observed. Conclusion: Lipomas on the fingers are rare occurrences that typically affect females, and the optimal surgical treatment involves complete removal of the tumor to achieve definitive healing. Despite their rarity, clinicians should consider lipomas in the differential diagnosis of soft tissue tumors in the hand. Cite this article as: Öner MB, Yalçın CE, Çelik U, Çınar F, Çomunoğlu N, Çetinkale O. Digital lipoma: Retrospective evaluation of cases in a reference center. Cerrahpaşa Med J. 2024;48(2):141-145.